A Rare Case of Spinal Schwannoma in a Child Presenting with Subarachnoid Hemorrhage: A Case Report with Review of Literature - Tanki, Humam (J Pediatr Neurosci, 2018)
Pediatric spinal schwannomas/neurofibromas constitute only 2.5%–4% of all pediatric spinal tumors. However, subarachnoid hemorrhage (SAH) because of spinal pathologies is very rare, representing 1.5% of all cases of SAH. Spinal nerve sheath tumors such as schwannomas rarely present with SAH, especially before the appearance of overt signs of spinal cord or root compression. We report a case of dorsolumbar schwannoma in an 11-year-old girl presenting clinically with signs and symptoms mimicking meningitis, but meningeal signs later proved to be due to SAH associated with spinal (D12-L1) schwannoma and hydrocephalus. Mass was excised and ventriculoperitoneal shunt was inserted. In our clinical practice, we may sometimes come across some uncommon diseases with even more uncommon presentations as happened with us at our institute. We must always consider that there is a possibility of SAH owing to silent spinal lesion in patients with angiographic negative intracranial SAH as in this case.